The effect of planting mode on the growth of pepper in a sunlight greenhouse. Issue 3 (March 2021) - Liu, Na; Wei, Zhengying; Wei, Haoran
Abstract: To adapt to the development of mechanization, a new mechanized planting mode is needed. Taking capsicum as the research object, a comparative test of mechanical east-west ridge planting mode and artificial north-south ridge planting mode was carried out in Hotan sunlight greenhouse with 2ZYZ-2 transplanter. The results showed that transplanting depth of 6 cm, row spacing of 30 cm and row spacing of 40 cm were the best working parameters of the transplanter. The plant height of artificial model pepper was 4.1% and 3.95% higher at 35 and 70 d, while the stem diameter of mechanized model pepper was 5.72% and 3.63% higher at 35 and 70 d. The difference was significant between them. However, the difference between the underground part of the two modes is small, while the accumulation of the mechanized part of the above ground is high and the characters are reasonable. The effective yield of mechanized mode is 2.38 t, which is 11.21% higher than that of manual mode. The two modes of pepper have the same nutritional composition. Therefore, the mechanized planting mode has certain advantages over the artificial planting mode and it can be used in Hotan sunlight greenhouse for pepper production.